1999
DOI: 10.5737/1181912x94175178
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer treatment: The benefit of patient telephone follow-up post-chemotherapy

Abstract: Approximately 2,500 women in Canada were diagnosed with cancer of the ovary in 1997 (NCIC, 1997). Standard therapy consists of surgical tumour debulking and cytotoxic chemotherapy. Very little data are available examining the most appropriate outpatient management of patients receiving chemotherapy. The objective of this study was to assess the impact of and benefit received from telephone follow-up between chemotherapy treatments for patients with cancer of the ovary. Patients with cancer of the ovary were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 4 publications
1
28
0
1
Order By: Relevance
“…Thus, the postdischarge telephone call allowed for rapid identification of new and potentially significant patient-reported problems requiring intervention. Our results are similar to those of Kelly et al, 9 who found that a telephone call was a valuable tool in assessing adverse effects and patient needs between chemotherapy treatments. The lower rate of ED visits and unscheduled readmissions within 30 days that we observed in the phone call group is a potentially important finding and warrants further study.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, the postdischarge telephone call allowed for rapid identification of new and potentially significant patient-reported problems requiring intervention. Our results are similar to those of Kelly et al, 9 who found that a telephone call was a valuable tool in assessing adverse effects and patient needs between chemotherapy treatments. The lower rate of ED visits and unscheduled readmissions within 30 days that we observed in the phone call group is a potentially important finding and warrants further study.…”
Section: Discussionsupporting
confidence: 91%
“…There has been little evaluation of telephone nursing services in Canada (Cooley et al, 1994;Hamilton & Grant, 2006;Kelly, Faught, & Holmes, 1999;Stacey et al, 2003;Wilson & Hubert, 2002). A systematic review of studies of telephone-based health services in primary care found that approximately 50% of the symptom calls could be managed by telephone alone without in-person visits and that nurses' care was equally as safe as physician care (Stacey et al).…”
Section: Conj • 17/4/07 Rcsio • 17/4/07mentioning
confidence: 99%
“…En plus de cette intervention de triage, les infirmières prodiguent également des conseils et de l'enseignement aux patients, des références vers d'autres ressources, un soutien psychosocial et les arrangements nécessaires à la prestation de services de soutien à domicile (Wilson et Hubert, 2002 (Cooley et coll., 1994;Hamilton et Grant, 2006;Kelly, Faught et Holmes, 1999;Stacey et coll., 2003;Wilson et Hubert, 2002). Un examen systématique des études portant sur les services de santé fournis au moyen du téléphone dans le domaine des soins primaires a permis de constater qu'environ 50 % des appels relatifs aux symptômes pourraient être gérés au moyen du téléphone sans visites en personne et que les soins infirmiers étaient aussi sécuritaires que les soins dispensés par les médecins (Stacey et coll., 2003).…”
Section: Contexteunclassified